Exchange Arrangements in Bulgaria after 1990: Floating and Fixed (Currency Board) - Nikolova, Irena (Economy and Business Yearbook, 2022)
Exchange rates and exchange arrangements are linked with all economic and financial indicators, and their change has an impact on various aspects of societies. Thus, the choice of an exchange arrangement is important for the economy planning. And change of an existing exchange arrangement with a new one in times of permanent crises increases risks for the stability of the economy. The existing exchange arrangements in the world are reviewed in the paper and the exchange arrangements in Bulgaria since 1990 are discussed as well.